PENYIMPANGAN KESETARAAN GENDER DALAM PENDIDIKAN - T, Hj. Fatimah (PSW, 2011)
Deviations of gender equality in education to be a problem if the blocking of jaccess, participation, control on involvement in the experience of the decision and the right to benefit from education. Deviation scan be seen in charge of textbooks, especially language and literature, social studies, CIVICS, physical education, and the like that discuss womanâs position in society tend to still embrace the values of gender bias.Woman in these books are still placed in domestic roles, where as men are placed in public roles. Thus the content of these books are still acknowledges the existence of a strict spatial separation between men and woman. The man in the public sphere while woman in the domestic sphere. Curriculum and learning materials that have not been referring to the principles of equality and gender justice will cause woman still do not have the mentality as productive citizens.